Konteks Historis turunnya Al-Qur’an: tahapan turunnya Al-Qur’an sebagai petunjuk umat Islam - Mufidah, Nur Ayny (Maliki Interdisciplinary Journal, 2025)
Grasping the historical context surrounding the revelation of the Qur’an is essential for comprehending the divine guidance imparted to the Prophet Muhammad (SAW), intended as a life compass for Muslims. The Qur’an was revealed in two primary phases: initially, it descended from Lauhul Mahfuzh to Baitul ’Izzah (the heavenly abode), and subsequently, it was revealed gradually to the Prophet over a span of approximately twenty-three years. This gradual unfolding was significantly shaped by various social, political, and spiritual events within the Islamic community of that time. Scholarly perspectives indicate that the first revelation occurred on the night of Lailatul Qadr during the month of Ramadan, followed by a series of revelations aligned with the pressing needs of the nascent Muslim community and the challenges of spreading the message of Islam. This incremental revelation offers practical and moral guidance that resonates with the circumstances faced by the people during that era. By delving into the historical context of the Qur’an’s revelation, Muslims can better appreciate its messages and integrate its teachings into their daily lives.